2019
DOI: 10.1159/000496225
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Resection and Ablative Treatment for Hepatocellular Carcinoma: Usefulness of Complementary Radiofrequency Ablation

Abstract: Aim/Background: In HCC patients with multiple tumors in separate segments, monotherapy with surgical resection is often difficult when the estimated residual liver volume after surgery is thought to be inadequate. We evaluated the usefulness of resection combined with low invasive radiofrequency ablation (RFA) for treatment of such cases. Materials/Methods: We analyzed 115 HCC patients with countable multiple tumors (≤5) without vascular invasion and/or extrahepatic metastasis, and treated solely with resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Again, there was no significant difference in the 5-year overall survival (65.6% and 67%; p = 0.244) or disease-free survival (23.3% and 28%; p = 0.257) between the two treatments, respectively. 8 It is promising to see that both approaches are comparable in overall and disease-free survival; however, a few studies reported recurrence at the site of ablation, which was not stated in the current study. The recurrence rate noted in the literature regarding the RFA sites was in the range of 16.7-20.5%, which is higher than to be neglected.…”
mentioning
confidence: 57%
“…Again, there was no significant difference in the 5-year overall survival (65.6% and 67%; p = 0.244) or disease-free survival (23.3% and 28%; p = 0.257) between the two treatments, respectively. 8 It is promising to see that both approaches are comparable in overall and disease-free survival; however, a few studies reported recurrence at the site of ablation, which was not stated in the current study. The recurrence rate noted in the literature regarding the RFA sites was in the range of 16.7-20.5%, which is higher than to be neglected.…”
mentioning
confidence: 57%